If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 25x + -3 = 35x + 5 Reorder the terms: -3 + 25x = 35x + 5 Reorder the terms: -3 + 25x = 5 + 35x Solving -3 + 25x = 5 + 35x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-35x' to each side of the equation. -3 + 25x + -35x = 5 + 35x + -35x Combine like terms: 25x + -35x = -10x -3 + -10x = 5 + 35x + -35x Combine like terms: 35x + -35x = 0 -3 + -10x = 5 + 0 -3 + -10x = 5 Add '3' to each side of the equation. -3 + 3 + -10x = 5 + 3 Combine like terms: -3 + 3 = 0 0 + -10x = 5 + 3 -10x = 5 + 3 Combine like terms: 5 + 3 = 8 -10x = 8 Divide each side by '-10'. x = -0.8 Simplifying x = -0.8
| 2p^3*6p^4= | | 20*.15= | | 8y-7-6y+2=0 | | 3x+27=20x-43 | | x/9+4=13 | | -9(x-4)+5x=-4(x+8)+5 | | 9*19+9= | | 2(4x+9)=-42+36 | | -x^2+8x-52=0 | | 12=4r-8+6r | | 4x-1(60-x)=130 | | 12/3x2/8 | | 1/2y-8=-7 | | 2+x=94 | | 7(y+9)+y=2(y+5)+4 | | 3x^2-12x-38=0 | | (12+8x)+13= | | 2x+5=7-2x | | 4th=60+10t | | 9x-5+3x+2= | | 3x^3-7x+6x-14=0 | | 0.3x=0.51 | | -3(2t-3)+2t=7t-3 | | 3xy+5x-2y+4yx+11x-8= | | -6z+4z=6z-8+7z | | 5x+2=-3+3x+17 | | (56/x-2)=x-3 | | (2/3)(x)+(1/2)(x-4)=x-4 | | 2y^2-15y-12=0 | | -22=-w-3 | | 2x+5=x+3(1-2x) | | 10-(3n-3)=1-4n |